Solutions to the inner ear problems - Curralo, Ana (2014)
The research related to hearing loss has caused a major advance in understanding lhe mechanisms that govern the development, function and response to injury and aging af lhe inner car. The purpose af this paper is to deseribe lhe solutions to the problems existing in lhe inoer ear hearing aids, as well as technological advances in research to overcame this problem and develop new more effective hearing implants.